(3GdeWGdH GdhGajI aj ahGFO GdcJH GdKeGfjIs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg LGeY GdTJGJ ef GdCMjGA hGdCehGJ CeG HYO aEf GdETJZGd HGdYde NUhUkG HGdMOjK GdfHhi ef CaVd GdbQHGJ hbO LeY CFeJfG efg GdSGQ Ydi GdeSGfjO hGdCHhGH GdeQJHGJ s
(3BNQgG (B:s
(3jfJgi HHGH BNQ ef jONd GdLfI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs